Estudio de la cultura organizacional en la Cooperativa Reina del Camino Chone y su relación con el desempeño de esta institución. - Saavedra Vélez, Yuliana Monserrate (2018)
The culture and the studies of the organizational performance are taking more and more relevance, this is how the measurement is an essential part in the strategic and organizational planning, it allows to control and manage the existing or new processes, under the criterion that what is not measured it is not controlled and therefore it is not improved, by studying the organizational culture in the cooperative Reina del Camino Chone, it was intended to establish the dimensions of Organizational Culture existing in the environment in order to measure its contribution to the performance of the institution. The study process required the application of a descriptive methodology, emphasizing the problematic question, supported by tools such as the questionnaire designed by the evaluation model proposed by Denison Consulting (2013), composed of 60 questions distributed in four dimensions that make up the internal and external focus; validated through the calculation of Cronbach's Alpha and use of statistical software such as SPSS and Microsoft Office Excel 2010. The viability demonstrated by the applied procedure allowed to generate viable results, from which it could be concluded that the evaluation instrument with a score of 0.937 shows a high level of reliability, where the state of involvement (3.88), consistency (3.69), adaptability (3.78) and mission (3.90) with average ratings, generate an average value of Culture Organizational of the Cooperativa Reyna del Camino of 3.81, which locates its performance as not optimal (regular) for the organization.